Emerging Issues in Fish Larvae Research (Springer International Publishing, 2018)
This book deals with the fundamentals of key physiological mechanisms involved in the development and growth of fish larvae. Chapters included show how the environmental and nutritional conditions are affecting the developmental process from its molecular basis and how these same conditions also influence the final characteristics of late larvae and fry. This volume provides recent findings on the importance of environmental rhythms, some specific nutrients and the adequate microbial environment in the developmental processes including recent results of current research projects.